2006
DOI: 10.1111/j.1439-0426.2006.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of peat moss released by a commercial harvesting operation into an estuarine environment on the sand shrimp Crangon septemspinosa

Abstract: Summary Current methods used in harvesting peat in eastern Canada have raised concerns regarding potential impacts of escaped peat particles on aquatic ecosystems. A study was carried out in Mill Creek, an estuarine tributary of the Richibucto River in New Brunswick, where peat originating from a commercial operation has accumulated over several years. The sand shrimp Crangon septemspinosa Say (1818) was selected to determine potential environmental stress related to presence of peat in the sediment because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In the case of SSC, even relatively low thresholds that are exceeded for a long time will have an impact on habitat (e.g. St-Hilaire et al, 2006;Ouellette et al, 2006). Sub-lethal impacts of sediments on fish populations can appear at low concentration levels if there is a long duration of exposure (Waters, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of SSC, even relatively low thresholds that are exceeded for a long time will have an impact on habitat (e.g. St-Hilaire et al, 2006;Ouellette et al, 2006). Sub-lethal impacts of sediments on fish populations can appear at low concentration levels if there is a long duration of exposure (Waters, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It was rapidly concluded that the peat originated from a peat harvesting site draining into Malpec Brook (MGI Limited 1994). Furthermore, Ouellette et al (2006) found that the proportion of peat (in volume) in the surficial sediment layer (0-15 cm) in Mill Creek increased from 30% in 1997 to 76% in 1999. Subsequently, St-Hilaire et al (2006 Questions remaining after these two studies include the following: Are the high SSC events found by St-Hilaire et al (2006) The present study was designed to answer those questions.…”
mentioning
confidence: 96%
“…These thresholds were frequently exceeded during runoff events. However, some authors state that the duration of high SSC events is as important as the concentration itself [53], and even relatively low thresholds exceeded for a long time will result in sub-lethal and behavioral effects such as stress and increased activity; reduction in the capacity to search for food; reduced growth and resistance to disease; physical abrasion; and obstructed gills [52][53][54][55]. Fox example, [53] reported that more than six days of exposure to values >10 mg L −1 generates moderate stress in juvenile and adult salmon, similar to a day of exposure to SSCs > 50 mg L −1 .…”
Section: Implications Of the Resultsmentioning
confidence: 99%